I survived the sinking of the titanic, 1912 eaudiobook - Tarshis, Lauren (I Survived, 2017)
The most terrifying events in history are brought vividly to life in this New York Times -bestselling series! Ten-year-old George Calder can't believe his luck — he and his little sister, Phoebe, are on the famous Titanic, crossing the ocean with their Aunt Daisy. The ship is full of exciting places to explore, but when George ventures into the first class storage cabin, a terrible boom shakes the entire boat. Suddenly, water is everywhere, and George's life changes forever. Readers will be transported by stories of amazing kids and how they survived!